Discrimination of wild and cultured Japanese eels based on otolith stable isotope ratios. (15th September 2017) - Kaifu, Kenzo; Itakura, Hikaru; Amano, Yosuke; Shirai, Kotaro; Yokouchi, Kazuki; Wakiya, Ryoshiro; Murakami-Sugihara, Naoko; Washitani, Izumi; Yada, Takashi; ,
Abstract: We successfully discriminated wild and cultured anguillid eels without artificial tagging. For the purpose of population restoration of anguillid eels, stocking has been widely conducted in the European Union (EU) and Japan, although the net benefits of stocking remain unclear. To evaluate the effectiveness of eel stocking for population restoration, the survival, growth, escapement, and reproduction of stocked eels should be tracked. In this study, we explored the potential of using otolith oxygen and carbon stable isotope ratios as a natural tag to discriminate between wild and cultured eels, because cultured eels are often stocked into natural rivers and lakes. A discrimination model was developed based on wild ( n = 95) and cultured ( n = 314) Japanese eels as a training dataset. The results of accuracy estimation based on leave-one-out cross-validation were 96.8%. We then tested the applicability of the model to stocked–recaptured eels ( n = 20); 100.0% were successfully identified as cultured eels, indicating that these eels spend their early continental phase in aquaculture ponds before stocking. This method could be widely applied to assess the effectiveness of eel stocking by determining the proportion of stocked eels among those captured from rivers, coastal areas, or spawning grounds.